Análise e comparação de métodos de estimativa da evapotranspiração de referência para a região de Pelotas (RS). - Hallal, Márcia Oliveira Curi (2012)
The knowledge of the value of the evapotranspiration of the plants determines the ammount of water that must be replaced in the culture so that there are no productivity wastes or attenuation. The values of the reference evapotranspiration are very variable because of the many estimative methods used and also because of the climatic variability of each region. In this sense, the objectives of this work were: to estimate the evapotranspiration using the Penman-Monteith method, considering it as standard due to its precision, and to analyze its values related to the precipitation occurred in the region, identifying the periods where there is necessity of irrigation; to estimate the reference evapotranspiration through indirect methods and compare them to the standard, identifying a simpler method that produces trustable results; to analyze the correlation of the meteorological variables with the standard method in order to identify the most influent variables and, from them, select a method that uses them, with an expression that allows local adjustments in the coefficients. With data of the years between 1971 and 2010 from the Agroclimatologic Station of Pelotas, it was estimated the reference evapotranspiration verifying that the annual average for Pelotas is 2.25 mm d-1. It was also observed that in the period between November 20th and January 20th the average decendial values of precipitation are lower than those of the reference evapotranspiration estimative. From the correlation between methods it was verified that the Blaney-Criddle method is the one that best fits to the standard in all the seasons of the year in all time scales analyzed. Finally, it was concluded that the most influent variables in the reference evapotranspiration for the region of Pelotas are the global solar radiation and the net radiation; and that the modified expression of the Jensen-Haise method, EToJHmod=Rs (0.013T + 0.176), shows good and very good performance, respectively, on summer and spring.